2020
DOI: 10.3126/njn.v17i2.30181
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of intracranial meningiomas

Abstract: Background: Meningioma comprises 25-30% of total central nervous system tumors detected. Ninety percent of meningiomas are benign, 6% are atypical, and 2% are malignant. Complete resection is often curative. Objectives: The objective of this study is to give ideas about the descriptive epidemiology, clinical presentation and histopathology of current scenario at National Neurosurgical Referral Center, Nepal. Methods: This is a prospective study from the period of January 2015 to September 2019 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The results of the demographic analysis of orbital meningioma (Table 1) showed that the disease was most prevalent among respondents aged 30-44 years. Orbital meningiomas usually occur in the 3-4 decades of life, as reported in recent findings that it was common in people aged 30-50 years [19], [20]. In this study, female respondents occupied the highest proportion or 90.9%, which confirmed the previous studies that 75.6% of orbital meningiomas happened to adult women [4], [21].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the demographic analysis of orbital meningioma (Table 1) showed that the disease was most prevalent among respondents aged 30-44 years. Orbital meningiomas usually occur in the 3-4 decades of life, as reported in recent findings that it was common in people aged 30-50 years [19], [20]. In this study, female respondents occupied the highest proportion or 90.9%, which confirmed the previous studies that 75.6% of orbital meningiomas happened to adult women [4], [21].…”
Section: Discussionsupporting
confidence: 91%
“…The incidence ratio of orbital meningioma in female to male is 3:1. The higher prevalence of meningioma is observed among postmenopausal women received exogenous hormone replacement therapy (e.g., contraception) compared to those without the therapy [20], [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation